The Effectiveness of Interpersonal Communication on Employees at Vocational High School YPLP PGRI 1 Makassar - Sazwani, Nurul; Jamaluddin, Jamaluddin; Niswaty, Risma (Universitas Negeri Makassar, 2020)
As human social beings in everyday life always want to relate to other humans. He wants to know the surrounding environment, even wants to know what is happening in him. This curiosity forces humans to communicate. This study aims to determine the effectiveness of interpersonal communication among employees at Vocational High School YPLP PGRI 1 Makassar. Therefore, to achieve these objectives researchers used data collection techniques with observation, questionnaires, interviews, and documentation with a population of 24 people. And the data is processed using the quantitative descriptive analysis to determine the extent of the effectiveness of interpersonal communication among employees at the Vocational High School YPLP PGRI 1 Makassar. The results of this study indicate that the Effectiveness of Interpersonal Communication among Vocational High School YPLP PGRI 1 MakassarÂ staff with indicators namely: openness with a percentage reaching 90.83 percent, empathy with a percentage reaching 90.56 percent, supportiveness with a percentage of 83.13 percent, positiveness with a percentage reaching 89.44 percent and equality with a percentage reaching 92.08 percent of all the indicators are in the very good category. This is demonstrated through overall data analysis which shows the percentage reached 89.08 percent, the value is in line with related observations made by researchers in the field.Â